Does education finance reduce the inequality of educational results? The mediation effect of shadow education - Ma, Yingqi; Jia, Wei; Wang, Jingxuan; Wang, Xuesong; Zhou, Yuanxiang; Yan, Zeran (Frontiers in Psychology, 2022)
Public education finance in China plays an important role in education equality. This study investigated two mediation effects with a generalized structural equation model that comprised the mediation effect of shadow education at the school, family, and individual levels and the moderating role of education finance. There was a strong association among heterogeneity factors, shadow education, and educational results, with shadow education playing a mediating role in math and English courses. Individual heterogeneity differences had a negative impact on equality in educational results through access to additional shadow education opportunities, while heterogeneous factors were mediated through shadow education, causing financial moderation effects, in turn affecting inequality in educational results. Finally, the moderation degree and direction of education finance varied significantly, with a greater moderation effect on household-level factors that lead to unequal educational results. Targeted efforts are required to regulate shadow education, which is key to the development of the education system.